Impact of CRM strategies towards customer loyalty: Impact of CRM strategies towards customer loyalty; with special reference to the customers of private hospitals in Colombo - Mathotaarachchi, Kamani; Sugathadasa, H.W.W.J.H.K.; Chandrasiri, B.M.U.S.B; Dilrukshi , K.Sandya; Jayamaha, T.D.D. Tharindu; Lowe, W.S. Anupama; Peiris, T.P.; Pushpakumara, G.R.D.E (IJRDO - Journal of Business Management, 2021)
The study is aimed to understand the impact of customer relationship management (CRM) practices and strategies on Customer loyalty. Many research work being carried out in Asia and Middle East on several service sectors, such as Banking, Telecommunication, beauty culture etc. Researchers selected the topic and given special reference to the private hospital sector is due to (a) increase in private hospital facilities in Sri Lanka (b) increasing purchasing power of people and (c) growing healthcare insurance schemes. The research attempt to examine the relationship between Customer Relationship management practices and strategies and the customer loyalty. The research area had to be limited to Colombo area as the majority of leading private hospitals available in Colombo area. Researchers adopted five CRM practices and strategies selected from previous studies to find the relationship with customer loyalty. Namely (a) Service access, (b) Interactive management, (c) Understanding customer, (d) Handling complaints and (e) Relationship development. 395 customers have responded either on Google questionnaire or hard copy of questionnaire. It included 53 personal interviews of patients who has gone through various major operations and mix of all age groups between 18 to over 60 years range. Findings of the study, confirm that there is a positive relationship between selected CRM practices and strategies towards customer loyalty, It is identified that the tested components, Service access, Interactive management, Understanding customer, Handling complaints and relationship development are having positive relationship with the dependent variable, Customer Loyalty within the private hospital services in Colombo area.